"We want to offer you peace of mind": Marketing of transnational commercial surrogacy services to intended parents. Issue 4 (2nd October 2017) - Gezinski, Lindsay B.; Karandikar, Sharvari; Levitt, Alexis; Ghaffarian, Roxanne
ABSTRACT: The purpose of this research study was to conduct a content analysis of commercial surrogacy websites to explore how surrogacy is marketed to intended parents. The researchers developed a template to code website data, and a total of 345 website pages were reviewed. Websites depicted surrogacy as a solution to a problem, privileged genetic parenthood, ignored the potential for exploitation, dismissed surrogates' capacity to bond with the fetuses they carry, emphasized that surrogacy arrangements are mutually beneficial, ignored structural inequalities, and depicted surrogates as conforming to strict gender roles. These framings introduce vulnerabilities to both intended parents and surrogate mothers.